ON THE REPRESENTATION OF MULTI-IDEALS BY TENSOR NORMS - Botelho, Geraldo; Caliskan, Erhan; Pellegrino, Daniel (CAMBRIDGE UNIV PRESS, 2011)
A tensor norm beta = (beta(n))(n=1)(infinity) is smooth if the natural correspondence (E-1 circle times ... circle times E-n circle times K, beta(n+1)) (E-1 circle times ... circle times E-n, beta(n)), where K = R or C. is always an isometric isomorphism. In this paper we study the representation of multi-ideals and of ideals of multilinear forms by smooth tensor norms.
Keywords: multi-ideals; tensor norms; POLYNOMIALS; Mathematics